Application of Vocal Techniques in Choir Training of Laruik Sanjo Song at SMKN 1 Padangpanjang - gusti randa, Agid; Hendri, Yon; Irwan, Irwan (Scoring: Journal of Film Music, 2024)
Application of vocal techniques to the singing of SMKN 1 Padangpanjang students. This training is specifically for choir groups at the school. The song chosen for this was a song entitled Laruik Sanjo. The song created by Januar Arifin was then popularized by the Gumarang orchestra. For the needs of students or student choir groups at SMKN 1 Padang Panjang, the song was rearranged. This song is arranged into three types of voices, Soprano, Alto, and Tenor. Then the abilities of students who are members of a choir group of ten people will be seen. To what extent are they able to apply good vocal techniques when singing? This research is qualitative research and is descriptive in nature. This research also applies supporting methods such as lecture method, demonstration method, training, and evaluation method.